The role of voluntary health insurance in frailty onset and progression among older and aging European adults: a survival analysis, 2013–2022 - Michele Sorrentino; Yamato Uejima; Giuseppina Affinito; Paolo Montuori; Raffaele Palladino (Frontiers in Public Health, 2026)
Background Frailty is a syndrome characterized by physiological decline and increased vulnerability to adverse health outcomes, including disability, hospitalization, and mortality In Europe, 5.8–27.3% of those aged ≥65 is frail, and up to 50.9% is pre-frail. With an aging population, and cuts to public health spending, erosion of universal health coverage is becoming more evident in European Health Systems. As a result, voluntary health insurance (VHI) is becoming more common, offering faster access and reduced out-of-pocket expenses. However, VHI may also widen health inequalities, as lower-income groups face greater barriers to care, delayed or missed care, and prevention, increasing their risk of becoming frail. Aim This study aimed to estimate the prevalence of VHI and assess its impact on the progression and onset of frailty among Europeans aged 50 and older between 2013 and 2022. Methods Data was retrieved from waves 5, 6, 8, and 9 of Survey of Health, Aging and Retirement in Europe (SHARE) dataset, a longitudinal panel study of adults aged 50 years and older. Frailty was assessed using the SHARE Frailty Instrument (SHARE-FI), which includes weight loss, exhaustion, grip strength, walking speed, and physical activity. Mixed effects linear regression and Cox proportional hazards regression were employed to assess the impact of VHI on frailty. To further assess whether the association varied across subgroups, analyses were stratified by income quartiles (Q1 to Q4 being the highest) and country of residence. Results At baseline 191,848 individuals aged 50 and above from 17 counties were included. VHI coverage was 37%, and increased across survey waves, with marked heterogeneity by country of residence and quartile of income. VHI was associated with lower frailty scores (coeff. = −0.056; 95% CI: −0.071 to −0.041) with the strongest association observed in Q1 (coeff.:= − 0.786; 95% CI: −0.817 to −0.755). Country-specific analyses confirmed this figure. When analyzing the risk of frailty onset ( n = 53,873; 311,695 person-years) 4,645 events were recorded. VHI was associated with a reduced risk of frailty onset (HR = 0.862; 95% CI: 0.763 to 0.973), particularly in Q2 (HR = 0.798; 95% CI: 0.667 to 0.955) and in Spain (HR = 0.626; 95% CI: 0.475 to 0.824). Conclusion VHI was associated with lower frailty progression and reduced risk of frailty onset. Nonetheless, being an out-of-pocket expense, it also might increase inequalities by weakening the Public Health System if not fully integrated into a wider strategy.